Glycemic index role on visceral obesity, subclinical inflammation and associated chronic diseases - Patricia Feliciano Pereira; Crislaine das Graças de Almeida; Rita de Cassia Gonçalves Alfenas (Nutrición Hospitalaria, 2014)
Background: It is believed that the glycemic index (GI) may be used as a strategy to prevent and control noncommunicable diseases (NCD). Obesity is a multifactorial condition, a risk factor for development of other NCDs. Among the different types, abdominal obesity is highlighted, which is essential for the diagnosis of metabolic syndrome, and it is related to insulin resistance, dyslipi-demia, hypertension and changes in levels of inflammatory markers. Such indicators are closely related to the development of Type 2 Diabetes and cardiovascular disease. Objectives: Discuss the role of GI as a strategy for the prevention and/or treatment of visceral obesity, subclinical inflammation and chronic diseases. Results and discussion: The intake of low GI diets is associated with glycemic decreases, and lower and more consistent postprandial insulin release, avoiding the occurrence of hypoglycemia. Moreover, consumption of a low GI diet has been indicated as beneficial for reducing body weight, total body fat and visceral fat, levels of proinflammatory markers and the occurrence of dyslipidemia and hypertension. The intake of low GI foods should be encouraged in order to prevent and control non-communicable diseases.